Growth kinetics of citrus Suhuiensis cell suspension cultures - Mohamad Puad, Noor Illi; Sarji, Muhammad Alif; M. Fathil, Nur Alia; Abduh, Muhammad Yusuf (IIUM Press, International Islamic University Malaysia, 2018)
Citrus is one of the major commodities in many countries including Malaysia. However, production of citrus including Citrus suhuiensis (C. suhuiensis) is declining due to diseases and inability to withstand low temperatures. Plant cultures such as cell suspension have the potential in propagating disease-free and healthy Citrus fruits with value-added characteristics. However, studies related to C. suhuiensis is still scarce. Therefore, the growth kinetics of C. suhuiensis cell suspension culture was studied. Friable callus of C. suhuiensis which was induced from seeds was inoculated into MS medium with 30 g/L sucrose, 0.5 g/L malt extract and 2.0 mg/L 2, 4-D for the cell suspension initiation. Several batch experiments using a few types of sugars (sucrose, glucose and fructose) were carried out. The cell dry weight (CDW) of C. suhuiensis was recorded for 30 days of culture period and residual sugars in the medium were analyzed using HPLC. Cells grown in 30 g/L sucrose achieved the highest CDW (9.559 g/L) with μmax equals to 0.00512/h, compared to glucose and fructose. In addition, sucrose is the preferred carbon source with the highest uptake rate (0.213 g/L·h). Cells completely hydrolyzed sucrose into glucose and fructose after 5 days of inoculation. All sugars were completely utilized by C. suhuiensis cells after 25 days. The kinetic growth parameters determined from batch experiments were then used for model simulation and verification in MATHCAD 15. After adjustments and refinement to the selected kinetic parameters, the model has fairly described and predicted the growth and sugars profile of C. suhuiensis cells. The proposed model can be used to predict sucrose hydrolysis, glucose and fructose formation from sucrose and their consumption by plant cells and also for larger scale of growth.